Influence and Consumption Pattern of Dairy Products on Nutritional and Health Development of School-aged Children in Ekiti Local Government Area of Kwara State, Nigeria (Sains Humanika, 2015)
This study examined the consumption pattern of dairy products among school-aged children in Ekiti local government of Kwara State, Nigeria. A questionnaire was used to elicit information from the students and multistage sampling technique was used to select 120 children. The 54 primary schools in the study area were stratified into 20 strata on the basis of the village demarcation in the study area. 6 pupils between primary five and six were randomly selected from each of the 20 schools. Frequency distributions, percentages and means were calculated. Pearson product moment correlation (PPMC) test was used to determine the relationship between some selected socio-economic characteristics of the respondents and their milk consumption frequency. Findings revealed that respondents’ preference for dairy consumption was more of milk alone and at other times combined with pap or beverages. Cheese, yoghurt and powdered milk were the most available dairy products. Also affordability was identified as the major constraint influencing the consumption of dairy products. The results further revealed significant relationship between dairy product consumption and house-hold size and position in examination of respondents. Therefore, the study recommends the introduction of nutritional education and school milk-programme to be sponsored by government and other stakeholders.
Keywords: Influence; consumption pattern; dairy products; development; school-aged; children